2019
DOI: 10.33314/jnhrc.v17i01.1534
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Related to Intrauterine Fetal Death

Abstract: Background: Intrauterine fetal death is a traumatic event. Stillbirth rate is an important indicator to assess the quality of antenatal care. The objective of the study was to identify the risk factors related to intrauterine fetal death in patients admitted with intrauterine fetal death.Methods: It was a descriptive study conducted in the department of Obstetrics and Gynaecology at B. P. Koirala Institute of Health Sciences from January to December 2014. Patients admitted with singleton pregnancy with intraut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…A relatively high number of patients had no identified risk factors. 13 Similar studies conducted in different health care centers of Nepal also found hypertension as a significant risk factor for IUFD. 4,14 Noteworthy, our study also showed similar results with a high incidence of hypertension complicating pregnancy followed by heart disease in mothers.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…A relatively high number of patients had no identified risk factors. 13 Similar studies conducted in different health care centers of Nepal also found hypertension as a significant risk factor for IUFD. 4,14 Noteworthy, our study also showed similar results with a high incidence of hypertension complicating pregnancy followed by heart disease in mothers.…”
Section: Discussionmentioning
confidence: 62%
“…This result is consistent with the findings of the study by Shrestha et al and Thakur et al where 66.67% and 53.3% of the babies born were preterms respectively. 13,20 A similar study done in Nepalgunj Medical College showed 63.07% of the cases of IUFD were preterm and it is a significant risk factor for IUFD. Congenital malformations were evident in four cases of IUFD and are also shown to be significant risk factor for IUFD in previous studies.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations